A conceptual database model for the identification of degraded areas and areas proposed for planned revitalisation - Podciborski Tomasz Stanisław; Zienkiewicz Aleksandra (Bulletin of Geography. Socio-Economic Series, 2021)
For revitalisation programmes to be effective, territorial governments have to introduce consolidated measures that support the planning, organisation and implementation of revitalisation measures to benefit local communities and economies, and to alleviate crisis situations in degraded areas. Such measures require unlimited access to data that accurately describe social, economic and environmental conditions. In view of the above, the main aim of this study was to propose a conceptual database model for the identification of degraded areas and areas proposed for planned revitalisation under revitalisation programmes implemented in urbanised rural areas. The detailed objectives of the presented research were to describe the components of the proposed database and the sources of data for developing municipal revitalisation programmes. A diagram of the database model supporting the initial stages of revitalisation was also presented. The research methodology involved analyses, inference and deduction. A questionnaire survey conducted among geography, spatial planning, urban development and environmental experts was used as a research tool in the study. The results of the questionnaire confirmed the validity of the components of the proposed database model.